Blended-learning model (b learning) in the reading skill - Sandoval Cuevas, Verónica Viviana (2023)
This research work aimed to determine the effect of the hybrid learning model (B learning) on reading ability. This research used the quantitative method through the collection of numerical data that was analyzed and calculated the information also quasi-experimental because by using a pre-test, a post-test was applied to obtain data. The results obtained showed that in the pretest the grades were similar between the control and experimental groups in the control it was 30.53% in the experimental group it was 30.70%. When the post-test was applied, the scores were significantly higher in the students who were part of the experimental group with 70.31%. The research level was descriptive statistics: mean, standard deviation, minimum and maximum values of the pre-test and post-test results obtained by the students.